2021
DOI: 10.3390/jcm10112256
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Lacer HaliTM Treatment on the Management of Halitosis: A Randomized Double-Blind Clinical Trial

Abstract: Background: Halitosis of oral origin is very common in the general population. Due to their antimicrobial properties, chlorhexidine-based products are widely used in the management of this condition, but these are associated with reversible side effects. In this study we evaluated the efficacy of Lacer HaliTM mouthrinse and toothpaste in subjects with intraoral halitosis after several applications under normal conditions of use. Methods: In this randomized clinical trial with mouth rinse and toothpaste, single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Previous studies used Scope® oral wash to preserve oral microbiome samples (Vogtmann et al ., 2019; Yano et al ., 2020), and its stability at room temperature was already verified (Vogtmann et al ., 2019; Wu et al ., 2021); however, it is not easily found in Europe. As chlorhexidine has been commonly used in many clinical trials where effective results have been proven in reducing the proliferation of bacterial species (Eick et al ., 2011; James et al ., 2017; Ben-Knaz Wakshlak, Pedahzur and Avnir, 2019; Brookes et al ., 2020; Sedghi et al ., 2021; Xiang, Rojo and Prados-Frutos, 2021), we opted for Lacer® Chlorhexidine oral wash to preserve the samples. To the best of our knowledge, the stability of Lacer® oral wash samples at room temperature has not been previously studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies used Scope® oral wash to preserve oral microbiome samples (Vogtmann et al ., 2019; Yano et al ., 2020), and its stability at room temperature was already verified (Vogtmann et al ., 2019; Wu et al ., 2021); however, it is not easily found in Europe. As chlorhexidine has been commonly used in many clinical trials where effective results have been proven in reducing the proliferation of bacterial species (Eick et al ., 2011; James et al ., 2017; Ben-Knaz Wakshlak, Pedahzur and Avnir, 2019; Brookes et al ., 2020; Sedghi et al ., 2021; Xiang, Rojo and Prados-Frutos, 2021), we opted for Lacer® Chlorhexidine oral wash to preserve the samples. To the best of our knowledge, the stability of Lacer® oral wash samples at room temperature has not been previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, as this solution is not easily found in Europe, Chlorhexidine oral wash (Lacer®) was used. Chlorhexidine has been commonly used in many clinical trials where effective results have been proven in reducing the proliferation of bacterial species (Eick et al ., 2011; James et al ., 2017; Ben-Knaz Wakshlak, Pedahzur and Avnir, 2019; Brookes et al ., 2020; Sedghi et al ., 2021; Xiang, Rojo and Prados-Frutos, 2021). Furthermore, the effect of daily use of chlorhexidine oral wash on the oral microbiome has been studied, showing significant differences in the abundance of some phyla (Bescos et al ., 2020) and a decrease in terms of alpha diversity compared with sputum samples (Chatzigiannidou et al ., 2020; Pragman et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“… 9 It was also reported that Lacer Hali TM could be used as an alternative to chlorhexidine based toothpaste and mouthwashes for the management of halitosis. 10 …”
mentioning
confidence: 99%